The dynamics of skills: Technology and business cycles - Valeria Cirillo; Mario Pianta; Leopoldo Nascia (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
This article investigates the role of technology, education and wages in shaping the skill structure of employment considering the upswings and downswings of business cycles. We develop an econometric estimation of these relationships and carry out an empirical test at the industry level for manufacturing and services for five European countries (Germany, France, Spain, Italy and United Kingdom) over the period 1999-2011, For the first time, these relationships are separately investigated in the specific contexts of the last upswing of Europe's business cycle (2002-2007) and of the post-crisis downswing (2007-2011) in order to assess the impact of cycles on employment and skill dynamics, and their determinants. Skills are investigated using ISCO professional groups, with a distinction between Managers, Clerks, Craft and Manual workers. We show that patterns of change of such groups are significantly different from one another and are appropriate to account for the evolution of the overall skill structure. Results document the role that different types of technological change, education, wages and demand have on industries' job creation, broken down by professional groups. In manufacturing all professional groups except managers experience job losses that are mainly driven by the introduction of process innovation. In services, a polarised employment structure emerges, mainly driven by the expansion of demand. These relationships, however, do not always hold. During the downswing most established links break down; in particular, product innovation loses its positive impact on jobs while new processes drive the process of restructuring that is taking place, with diverse effects on each professional group.
Keywords: J23; J24; J21; O3; 330; Skills; Innovation; Technology; Business Cycles